FAMILY LAW POLITICS IN INDONESIA FROM THE PERSPECTIVE OF MOH. MAHFUD MD'S DIALECTICAL RELATIONSHIP THEORY - Suaidah Nasution; Dodi Ferdiansyah; Abdul Qodir Zaelani (Politea : Jurnal Politik Islam, 2026)
Islamic family law politics in Indonesia develops through complex dialectical interactions between religion, state, local culture, and national legal reform movements. This complexity is intensified by diverse Islamic legal schools and political currents seeking either formalization or substantivization of Islamic law within the national system. This article analyzes these dynamics using Moh. Mahfud MD’s dialectical relationship theory, focusing on how Islam, the state, and culture shape the formation and reform of family law. This study employs normative legal research with conceptual and historical approaches, examining primary and secondary legal materials on Islamic family law and Mahfud MD’s theory. The findings show that Islamic family law evolves through a selective positivization process guided by cultural and substantive approaches integrating Islamic values into the Pancasila constitutional framework without requiring a formal Islamic state. Key legislation such as the Marriage Law (1974), Religious Courts Law (1989), and Compilation of Islamic Law (KHI) reflect a productive synthesis between Islamic norms and national law. Thus, Islamic family law in Indonesia develops through dialectical negotiation rather than unilateral Islamization, with Mahfud MD’s framework offering a reconciliatory paradigm for embedding Islamic values within the national legal system.